ISOLATION, CHARACTERIZATION AND PREDICTION OF BIOLOGICAL ACTIVITY OF TWO NEW FATTY ESTERS AND A PHENOL FROM THE HEARTWOOD OF PTEROCARPUS MARSUPIUM ROXB. - Katiyar, Deepti; Singh, Vijender; Ali, Mohammed (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The current investigation involves the isolation, characterization and prediction of biological activity spectra of the phytoconstituents from the ethanolic extract of the heartwood of Pterocarpus marsupium roxb. (Fabaceae). Methods: The heartwood (3 kg) was extracted in alcohol by cold maceration for 21 d and the compounds were isolated by column chromatography. The compounds thus isolated were characterised and their structures were elucidated by using assorted spectral data analysis, i.e., infrared radiation spectroscopy (IR), proton nuclear magnetic resonance (1HNMR), carbon thirteen nuclear magnetic resonance (13C NMR) and direct analysis in real time mass spectrometry (DART-MS). PASS (prediction of activity spectra for substances) computer program was used to predict the biological activity spectra of the isolated compounds. Results: Phytochemical investigation of ethanolic extract of the heartwood of Pterocarpus marsupium led to isolate two fatty esters and a phenolic compound characterised as n-octanyl n-octadeca-9,12-dienoate (n-octanyl linoleiate, 1), n-dodecanyl n-octadeca-9,12-dienoate (n-dodecanyl linoleiate, 2) and 2, 3-dioxymethylene phenol (3). These phytoconstituents are reported for first time in the heartwood of Pterocarpus marsupium Roxb. The in silico profiling of these phytoconstituents exhibited their broad spectra of biological activity. Compounds (1) and (2) showed their maximum activity as All-trans-retinyl-palmitate hydrolase inhibitor, anti eczematic, lipid metabolism regulator, etc. and compound (3) was found to be active as membrane integrity agonist, aspulvinone dimethylallyl transferases inhibitor, carminative, neurotransmitter uptake inhibitor, etc. Conclusion: These isolated phytoconstituents can be used as the marker compounds to establish the identity, quality and purity of the drug. The results of PASS prediction shall be very useful for establishing these phytoconstituents as active pharmacological moieties.